Staying on the Team: Public Health Nurse Retention and Mentorship - Wanous, Christine E (East Carolina University)
Research Problem and Objectives The well-being of the public health nurse workforce is in jeopardy due to national funding, demographic trends and workplace factors. Public health nurse attrition negatively affects public health agencies and the communities they serve. This study investigated what relationships five aspects of mentorship may have with the retention intentions of public health nurses. Methods Independent variables of mentor structure (formal vs. informal), mentor network type, racial concordance with mentors, supervisors as mentors and being a mentor were studied to determine any relationship they had with the outcome variable of public health nurse retention. The five quantitative research questions and other data were analyzed using Fisher’s Exact Test and logistic regression modeling. A cross-sectional sample of 526 current and former public health nurses were surveyed in the summer of 2024 regarding their mentorship and supervisor experiences, and retention intentions or reasons for leaving. Limited qualitative data was coded into themes and sub-themes. Key Findings In the study, 17.2% of current PHNs planned to leave their employer in the subsequent twelve months. The top reasons public health nurses for leaving voluntarily included burnout, leadership concerns and low pay. Public health nurses who had a mentor-like supervisor had higher retention intentions (88%) than public health nurses without a mentor-like supervisor (67%) (odds ratio = 3.1; adjusted p-value = 0.002). Millennial public health nurses had the highest leave intentions of any generation at 43% compared to GenX and Baby Boomer public health nurses at a rate of 16% (odds ratio = 3.85; unadjusted p-value = 0.0004). Formal mentorship showed some promise for public health nurse retention while being a mentor indicated a possible attrition risk. Conclusion Mentor-like supervision and formal mentorship programs may be good strategies for public health agencies to cultivate to improve public health nurse retention. An elevated leave intention rate of Millennial public health nurses suggests that public health agencies have work to do to satisfy this group of nurses. While mentoring programs can be beneficial for public health nurse mentees, being a mentor may have attrition risks that warrant strategic planning by public health leaders. Finally, retired and former public health nurses are underexplored workforce groups that may be open re-recruitment with the right position opportunities.
Keywords: Health Sciences, Public Health; Health Sciences, Nursing